(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
A very common understand of the word caryā brings to our mind often heard of the vajrayāna religious song known to us as caryāgīti accompanied by caryānŗtya. An apparently outward symbolic representation of the word in song and dance finds a deeper meaning when dwelt in depth. A thorough investigation into caryā opens up vast insight of vajrayāna philosophy and doctrines amalgamated in rituals of vajrayāna religious practice composed of sādhana, maņđala, mantra and mudrā with ultimate aim of emancipation in the present life itself. In essence a yoga practice with intricate procedures leads sentient beings to the world of spiritualism composed of esoteric ritual practices with a touch of aesthetical experience inherent in caryāgīti and caryānŗtya.